(untitled) (Journal of Parents and Teachers, 2021)
Don Bosco, guided by a dream and challenged by the reality he lived in 19th century Turin, was able to provide an educational response to the needs of young people through his preventive system. The creation of the workshops and his concern for the world of the working class would, over time, make vocational training will become a hallmark of the Salesians and John Bosco will become the patron saint of vocational training in our country.